Tipologi Peradilan Hukum yang Beradab: Suatu Kajian Epistemologis Teori Peradilan Hukum - Rahmatullah Ayu H. (UIR Press, 2022)
Adab and morals are an outstanding value as the essential characters of “ The Legal Justice” thinking, the moral term is officially used in West terminology while Adab is used in the Islamic world. Both Moral and Adab are used as society’s behavioral guidance besides the norms ( law), from this perspective the term“ civilized legal justice” is known. The different of concepts, principles, and thoughts of legal justice brings out the dilemma of human belief in the essentials of justice itself. Ethics and moral values ​​as the behavioral's benchmark of the norm as the tool of social engineering give the essential ambiguity when it is implemented in different views because justice is inseparable from the norms and moral values. The idea of ​​justice from the west, east, and Islam is a typology of struggle that shows a continuous effort to seek justice. What kind of justice can resolve the dilemmas and ambiguities of the existing essence of justice, or how should justice be able to maintain its concepts and principles in order to realize the happiness of all mankind in the present and future? This study aims to construct a legal justice based on a general concept, namely the thinking of justice from the west, east, and Islam. Where each type of thought has different concepts, characteristics, and essences so it is interesting to study more deeply.